Integration of Scratch Media in Mathematics Learning to Improve Computational Thinking Skills of High School Students - Naim, Muhammad Ainun; Rizkiya, Nur Bella; Rahmatullah, Jindan (Universitas Muhammadiyah Malang, 2025)
With the vision of realizing Indonesia Emas in the current digitalization era, computational thinking skills are an urgent need in learning, including in mathematics. Scratch, as a mathematics learning medium, offers a relevant approach to developing students' computational thinking skills. This study aims to review the literature related to the use of Scratch as a mathematics learning medium to improve students' computational thinking skills. The methodology used is a literature study consisting of three stages: compilation, synthesis, and identification. Based on the results and discussion, it was found that Scratch has a significant influence in improving students' computational thinking skills. This is shown through the development of students' computational thinking skills by using Scratch as a mathematics learning medium. This study suggests the need for more research on the use of Scratch in mathematics learning to produce more innovative and optimal results. Thus, the integration of technology in mathematics learning can make a major contribution to improving the quality of education and students' readiness to face future challenges.